Effectiveness of some Traditional and Non-Traditional Protection Measures on the Recovery of Uzi-Infested Eri Silkworm - Sarma, A. K.; Gupta, M. K. (Journal of Biological Control, 2008)
An attempt was made to study the effectiveness of some traditional and non-traditional protection measures on the recovery of eri silkworm parasitized by uzi fly, Exorista sorbillans (Wiedemann). Maximum recovery was obtained in bamboo-sieve (71,15%), followed by uzinet (60.51%), bleaching powder (2%) solution (3S.41%) and neem leaf extract (33.83%), as against untreated control (14.79%). Physical barriers may be recommended for higher recovery of uzi-infested eri silkworms.